2017
DOI: 10.1021/acs.biomac.7b01313
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Enzymatic Polymerization from Surfaces with Switchable Bioaffinity

Abstract: The affinity of surfaces toward proteins is found to be a key parameter to govern the synthesis of polymer brushes by surface-initiated biocatalytic atom transfer radical polymerization (SI-bioATRP). While the "ATRPase" hemoglobin (Hb) stimulates only a relatively slow growth of protein repellent brushes, the synthesis of thermoresponsive grafts can be regulated by switching the polymer's attraction toward proteins across its lower critical solution temperature (LCST). Poly(N-isopropylacrylamide) (PNIPAM) brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…More recently, aldol reactions were performed using Rhizopus arrhizus lipase [43]. Additionally, aqueous miniemulsions have been reported as environmentally benign enzymatic reaction media for polymerization [37,44]. In these polymerization media, there is no need to dry reagents before the polymerization, the water produced in dehydrative polyesterification is expelled to the continuous (aqueous) phase, and the biocatalyst stability is improved in comparison to an organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, aldol reactions were performed using Rhizopus arrhizus lipase [43]. Additionally, aqueous miniemulsions have been reported as environmentally benign enzymatic reaction media for polymerization [37,44]. In these polymerization media, there is no need to dry reagents before the polymerization, the water produced in dehydrative polyesterification is expelled to the continuous (aqueous) phase, and the biocatalyst stability is improved in comparison to an organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of GOx improved the fouling resistance of the polymer materials. Bruns et al found that the enzyme mediated surface-initiated biocatalytic atom transfer radical polymerization (SI-bioATRP) could be used to prepare PNIPAAm brushes [ 147 ]. This method provided a new way for the translation of bioadhesion into a controlled functionalization of materials.…”
Section: The Enzyme Mediated Atrp Systemmentioning
confidence: 99%
“…7,[16][17][18] We found that horseradish peroxidase (HRP) catalyzed the polymerization of N-isopropylacrylamide (NIPAAm) under activator regenerated by electron transfer (ARGET) ATRP conditions 16 whereas di Lena and coworkers showed that laccase and catalase could initiate polymerizations of poly(ethylene glycol) methyl ether methacrylate (PEGMA). 17,18 Since then, our group and others have demonstrated that metal-containing enzymes such as HRP, [19][20][21][22] laccase, 19,23 hemoglobin, [24][25][26][27] and catalase 19,28 can act as ATRP catalysts with distinct advantages, such as the ability to control the polymerizations of difficult monomers, which traditional ATRP conditions fail, 23 to confine polymerizations into nanoreactors, 20,21 to prepare biosensors, 26,27 and to tune surface-initiated polymerizations by the protein affinity of surfaces. 25 Metalloenzymes can be deduced to their cofactors, which also have been shown to catalyze ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Since then, our group and others have demonstrated that metal-containing enzymes such as HRP, [19][20][21][22] laccase, 19,23 hemoglobin, [24][25][26][27] and catalase 19,28 can act as ATRP catalysts with distinct advantages, such as the ability to control the polymerizations of difficult monomers, which traditional ATRP conditions fail, 23 to confine polymerizations into nanoreactors, 20,21 to prepare biosensors, 26,27 and to tune surface-initiated polymerizations by the protein affinity of surfaces. 25 Metalloenzymes can be deduced to their cofactors, which also have been shown to catalyze ATRP. [28][29][30][31][32][33][34] For example, Matyjaszewski and coworkers reported RDRP of methacrylates in aqueous solutions mediated by synthetic analogs of hemin and mesohemin, which were modified with 2-methoxy poly(ethylene glycol) (MPEG).…”
Section: Introductionmentioning
confidence: 99%